1993
DOI: 10.1063/1.860902
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic backward-wave oscillators operating near cyclotron resonance

Abstract: Microwave sources based on backward-wave oscillators (BWO’s) driven by relativistic electron beams are capable of producing high-power coherent radiation in the cm and mm wavelength region. When the axial magnetic field used in these devices to confine the electron beam satisfies the condition of cyclotron resonance there is a significant modification in the behavior of BWO due to beam coupling to cyclotron modes. In this paper a time-dependent, self-consistent theory of BWO’s is developed, taking into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…Additionally, the measured resonant magnetic fields of this article may differ from those of previous works ͑see Refs. 1,4,9,12,14, and 20͒ because the experiment design parameters of this article are different. Similarly, one can obtain the other theoretically predicted value of the resonant magnetic field using the design parameters of our experiment; therefore, B 2 res is about 12.0 kG.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the measured resonant magnetic fields of this article may differ from those of previous works ͑see Refs. 1,4,9,12,14, and 20͒ because the experiment design parameters of this article are different. Similarly, one can obtain the other theoretically predicted value of the resonant magnetic field using the design parameters of our experiment; therefore, B 2 res is about 12.0 kG.…”
Section: Discussionmentioning
confidence: 98%
“…Many authors [1][2][3][4][5][6][7][8][9][10][11][12] have focused their attention on this device for more efficient operation at high-power levels, and important results have been obtained both experimentally and theoretically. In order to further enhance the output power of microwave and the conversion efficiency of electron beam to microwave radiation, some scientists [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have introduced background plasmas into the BWOs, and both theoretical and experimental results have demonstrated that the background plasmas improve the beam-waveguide interaction dramatically.…”
Section: Introductionmentioning
confidence: 96%
“…[53], the cyclotron dip calculated numerically and measured experimentally is shown. References [53] and [54] considered the cyclotron resonance with the zeroeth spatial harmonic of the backward wave. As was"mentioned in the beginning of this subsection, the cyclotron resonance with the zeroeth harmonic of the forward wave is also possible, as shown in Fig.…”
Section: Cyclotron Resonance Effectsmentioning
confidence: 99%
“…14, taken from Ref. [53], the cyclotron dip calculated numerically and measured experimentally is shown. References [53] and [54] considered the cyclotron resonance with the zeroeth spatial harmonic of the backward wave.…”
Section: Cyclotron Resonance Effectsmentioning
confidence: 99%
See 1 more Smart Citation